2011
DOI: 10.1186/1475-2875-10-117
|View full text |Cite
|
Sign up to set email alerts
|

Respondent-driven sampling on the Thailand-Cambodia border. II. Knowledge, perception, practice and treatment-seeking behaviour of migrants in malaria endemic zones

Abstract: BackgroundPopulation movements along the Thailand-Cambodia border, particularly among highly mobile and hard-to-access migrant groups from Cambodia and Myanmar, are assumed to play a key role in the spread of artemisinin resistance. Data on treatment-seeking behaviours, knowledge and perceptions about malaria, and use of preventive measures is lacking as characteristics of this population prevent them from being represented in routine surveillance and the lack of a sampling frame makes reliable surveys challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 12 publications
(15 reference statements)
6
51
1
Order By: Relevance
“…This observation is consistent with the previous finding during the MARC survey [1]. As observed in other studies [16], self-medication practices were common, andthe private sector was typically preferred over the public sector. The majority of the migrant workers reported to rely on cocktail mixtures of drugs or artemisinin monotherapy, rather than prescribed ACT, freely available in the unregulated private sectors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with the previous finding during the MARC survey [1]. As observed in other studies [16], self-medication practices were common, andthe private sector was typically preferred over the public sector. The majority of the migrant workers reported to rely on cocktail mixtures of drugs or artemisinin monotherapy, rather than prescribed ACT, freely available in the unregulated private sectors.…”
Section: Discussionsupporting
confidence: 93%
“…Although the majority of the migrant populations understood Myanmar language, limited education level may impede their understanding of the message [11]. As shown in other studies conducted in similar circumstances [8,14-16], these physical, social and language barriers in the study population likely increase the potential risk in malaria transmission and spread of artemisinin resistance. Effective communication in this diverse high-risk group is critical and may be better reached by the use of simple language, inclusion of common ethnic languages in addition to Myanmar, and/or well-trained motivated interpreters.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies in Myanmar and on the Thai-Cambodian border found that malaria treatment was often delayed in remote areas. 25,26 Because jhum cultivators often work in large groups at various phases of cultivation, lack of prompt malaria treatment may facilitate local malaria outbreaks that can later be spread when jhum cultivators return to their villages.…”
Section: Discussionmentioning
confidence: 99%
“…In October 2009, an RDS study on migrant workers was carried out in Thailand along the Thai-Cambodia border and later a similar study was implemented in Cambodia to better understand internal migration patterns in two provinces on the border in the context of artemisinin resistance [10,11]. While there have been some studies along the northern stretch of the Thailand-Myanmar border [1214], relatively little is known about migration along the southern portion of the border, which is believed to be a significant port of entry for many migrants from Myanmar.…”
Section: Introductionmentioning
confidence: 99%